Ten years risk assessment of cardiovascular events among adult population visiting urban health and training centre of a tertiary care institution, Farrukhabad, Uttar Pradesh, India - Alam, M. N.; Khatoon, Shagufta (International Journal Of Community Medicine And Public Health, 2021)
Background: Cardiovascular diseases (CVDs) are the number one cause of death globally, four out of five CVDs deaths are due to heart attacks and strokes, and one third of these deaths occur prematurely in people under 70 years of age. In view of above background study conducted with the aim and objective to determine Ten years risk assessment of cardiovascular events (myocardial infarction or stroke) among adult population visiting UHTC of a tertiary care Institution, Farrukhabad, UP, India. Methods: A cross-sectional study was conducted using World Health organisation (WHO)/International Society of Hypertension (ISH) tool at urban health and training centre (UHTC) of a tertiary care institution at Farrukhabad, UP from August 2017 to January 2018. Sample size was 400 (n=4pq/l2). Ethical clearance was obtained from institutional ethical committee and written informed consent obtained from the participants. Data analysed using SPSS Software. Chi-square test used to observe level of significance at p<0.05. Results: Majority (69.5%) have less than 10% risk for CVD whereas 10.5% have 10-20% risk, 8% people have 20-30% risk, 6.25% have 30-40% risk and 5.75% people have ≥ 40% risk. Majority (58.75%) belong to young adult. About 7.75% people were diabetic and 11.25% were smoker. Concerning serum cholesterol, 49% had 5 mmol/l, 42% had 4 mmol/l, 0.75% had ≥8 mmol/l. Statistically significant association observed between socio-economic status (SES) and cardiovascular event when chi-square is 95.344, and p<0.00001. Conclusions: About 1/3 population have risk above 10%. Mostly middle-income group are on risk.